Self-Concept and Well-Being in HIV/AIDS Patients - Fenska Narly Makualaina; Cristyn Evangelin Watunglawar; Fathia Fakhri Inayati Said; Nofita Dewi Kok Mesa; Dwi Ayu Astuti; Minnalia Soakakone (GLOBAL HEALTH SCIENCE GROUP, 2026)
People with HIV/AIDS often experience disturbances in their self concept and well being. A low self concept can cause people with HIV/AIDS to feel worthless, insecure, and hopeless about the future. Low well being can also cause people with HIV/AIDS to experience stress, anxiety, and depression. This study aims to determine the relationship between self-concept and well being variables in HIV AIDS patients. The sampling technique in this study used total sampling with a sample of 35 respondents. Data were collected using questionnaires that had been tested for validity and reliability, which were self-administered by the respondents. The analysis test used Spearman's rho with a p-value of < 0.005. The results of the analysis showed that there was a significant relationship between self-concept and well-being in HIV AIDS patients (sig value = 0.001, p < 0.05). The correlation coefficient (r) was 0.543, indicating a strong positive correlation. Self-concept has a significant relationship with subjective well-being in HIV AIDS patients, which means that HIV AIDS patients who have a positive self concept are more likely to have higher subjective well being.